2023
DOI: 10.21203/rs.3.rs-2540742/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of different colorectal cancer screening strategies: a long-term passive follow-up population-based screening program in Beijing, China

Abstract: Background We aimed to assess the performance of the risk assessment questionnaire and fecal immunochemical test (FIT) in a population-based colorectal cancer (CRC) screening program to provide timely evidence for tailored screening strategies in China. Methods This analysis was conducted using data from Beijing Cancer Screening Prospective Cohort Study (BCSPCS). A risk assessment questionnaire and FIT were selected as the primary screening methods, and participants with any positive results were referred to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Studies from one of the CanSPUC screening sites (Beijing) indicated that the uptake rates of GC and CRC screening was 15.9% 53 and 25.2% 54 , respectively. The uptake rate of CRC screening in Beijing rural areas was higher than urban areas (58.9% vs. 25.2%) 55 , possibly because rural areas have adopted a combined strategy of FIT and questionnaires for high-risk population assessment 56 . However, the overall uptake rate of national digestive system cancer screening is low, and patient compliance directly affects screening effectiveness 57 .…”
Section: Identification Of High-risk Individualsmentioning
confidence: 93%
“…Studies from one of the CanSPUC screening sites (Beijing) indicated that the uptake rates of GC and CRC screening was 15.9% 53 and 25.2% 54 , respectively. The uptake rate of CRC screening in Beijing rural areas was higher than urban areas (58.9% vs. 25.2%) 55 , possibly because rural areas have adopted a combined strategy of FIT and questionnaires for high-risk population assessment 56 . However, the overall uptake rate of national digestive system cancer screening is low, and patient compliance directly affects screening effectiveness 57 .…”
Section: Identification Of High-risk Individualsmentioning
confidence: 93%